Antimalarial drug discovery – the path towards eradication. Issue 1 (17th July 2013) - BURROWS, JEREMY N; BURLOT, EMILIE; CAMPO, BRICE; CHERBUIN, STEPHANIE; JEANNERET, SARAH; LEROY, DIDIER; SPANGENBERG, THOMAS; WATERSON, DAVID; WELLS, TIMOTHY NC; WILLIS, PAUL
SUMMARY: Malaria is a disease that still affects a significant proportion of the global human population. Whilst advances have been made in lowering the numbers of cases and deaths, it is clear that a strategy based solely on disease control year on year, without reducing transmission and ultimately eradicating the parasite, is unsustainable. This article highlights the current mainstay treatments alongside a selection of emerging new clinical molecules from the portfolio of Medicines for Malaria Venture (MMV) and our partners. In each case, the key highlights from each research phase are described to demonstrate how these new potential medicines were discovered. Given the increased focus of the community on eradicating the disease, the strategy for next generation combination medicines that will provide such potential is explained.